COLLECTION OF LATGALIAN CERAMICS IN A VIRTUAL MUSEUM - Atpile-Jugane, Ineta (Via Latgalica, 2014)
This article is result of project “The Virtual Past is a Keystone for the Future of Museums”(LLB-2-269). Latgale Culture and History Museum (LCHM) plays an important role in preservation and promotion of ceramics of Latgale (LCHM has had one of the largest and most purposefully developed collections of ceramics of Latgale in the museums of Latvia since 1960) and in the development of the collection of Latgale ceramics by researching and exhibiting collections of ceramic items, recording potters’ biographies, documenting pottery inheritance and processes of creating ceramics in many Latgalian ceramic masters’ workshops. A part of Latgalian ceramic collection items are exhibited in the regular exhibition of Latgalian ceramics “The wonder created by clay and fire transformations”, but the other part is available in a virtual museum (www.futureofmuseums.eu), where the gallery is represented by 500 objects of LCHM collection of Latgalian ceramics. It includes a relatively wide range of works and types of dishes, created by ceramic masters of Latgale (vases, jugs, whistles, plates, money-boxes etc.). Alongside the works, created by Latgale ceramic classics, there can be viewed experiments developed by contemporary ceramists of Latgale, which reveal the search for a new path that allows people to discern the development of ceramics of Latgale. To increase the interest in ceramics of Latgale and to get acquainted with the traditions, the virtual museum visitors are offered to participate in a creative educational game “Clay transformations”, during which anyone can be a virtual potter – a clay master, by experiencing clay transformation path from its preparation till the burned piece of art. Everyone may optionally either only create pottery, or parallel to the creation of the dish can learn many interesting facts about the potter’s work and its specifics. Virtual museum is still one of the options to ensure availability of collections to society and tell a wider audience (especially to young people) about the museum, its work, Latgale ceramics and traditions in a modern and interactive way.